Smart Wearable EEG Sensor - Kannan, R. (Elsevier B.V., 2017)
Currently, traditional and ambulatory EEG systems are beyond ideal for patients suffering from different brain diseases. Traditional monitoring of electrical activity in a diseased brain is limited to the clinical environment where patients being put away from natural environment in which provoking factors of abnormalities in the electrical activity of the brain are more likely to occur. Similarly, ambulatory EEG systems have a drawback of being cumbersome and impose some restrictions on the patient, such as not being able to show in public due to the social acceptability of wearing such a head-mounted device. The will of the patients to not publicizing their disorder or illnesses is a major drawback for current EEG system to be widely adopted. This paper presents an attempt to develop a wearable EEG prototype using off-the-shelf components to record EEG signal from the ear and display the obtained brain signals in the LabVIEW software. The developed prototype was able to record Ear-EEG in real-time. © 2017 The Authors.